Persistence of a hypoglossal artery: Case report - Abdullah Ali AlQarni; Talal AlOtibi; Yahya Mahnashi; Abdullah Alawad; Waleed Mohammed Aldawsari (Radiology Case Reports, 2024)
Persistent primitive hypoglossal artery (PPHA) is a rare embryological carotid–basilar anastomosis. Diagnosis is by imaging and computed tomography angiography is the most common methods employed. Herein we present a case of a 51 years-old Indian male, who admitted with midnight nonwitnessed syncope. CT angiogram of the brain revealed a very rare caroto-basilar anastomoses anomaly with PPHA.